Performance Analysis of Hybrid Optical Access Networks That Combine Fiber to The Home (FTTH) and Radio Over Fiber (RoF) Using Wavelength Division Multiplexing (WDM) for Network Efficiency - Febrizal Ujang; Aguinaldo Al Nazen (Universitas Ahmad Dahlan, 2024)
Today, people's need for communication has increased and telecommunication services have become basic needs in life. Therefore, broadband transmission system services are needed to support the quality of information flow between customers and the number of customers need access to available information. Fiber optic communication system is one that can be used to overcome these problems because it is very efficient and has high bandwidth. This system has several types of applications including for Fiber to the Home (FTTH) and Radio over Fiber (RoF). Usually, these two network systems are built separately, so the study of merging these two systems into a hybrid network is needed for future network efficiency. In previous research, several types of network combinations were carried out using the same wavelength, so they had to create separate components. In this research, a hybrid network design simulation was carried out using optisystem software that combines FTTH and RoF using Wavelength Division Multiplexing (WDM) so that only need to utilize existing components, then performance analysis was carried out in the form of power, Q factor, and Bit error rate (BER). WDM was chosen for several considerations, including increasing capacity, reducing costs, flexibility and scalability. The network is simulated using an OptiSystem, there is an FTTH system from transmitter to receiver consisting of OLT, ODF, ODC, ODP, to the ONT or customer device. Then there is the RoF system to support Wireless Gigabyte (WiGig) communications using QAM modulation. From the simulation carried out by varying the length of the fiber cable, the results of the FTTH network can be said to be suitable for meeting good performance parameters where the simulated performance value in the form of Q factor meets the performance feasibility standard of 6 and the BER is above 10-9, while the RoF at long certain cable system performance has not met feasibility. But overall, the hybrid system using multiplexing offered can work with the expected performance.